Structural and functional evaluation of single-chain Fv antibody HyC1 recognizing the residual native structure of hen egg lysozyme. Issue 2 (1st February 2020) - Yamaoka, Takanori; Kamatari, Yuji O.; Maruno, Takahiro; Kobayashi, Yuji; Oda, Masayuki
ABSTRACT: Evaluation of the molecular mechanisms by which an antibody recognizes a specific antigen could help in better understanding of the protein recognition mechanisms. We previously showed that anti-hen egg lysozyme (HEL) monoclonal antibody, HyC1, recognized the structural and hydrodynamic change in HEL. Here, we generated HyC1 single-chain Fv (scFv), and characterized it using different structural and biophysical methods. Similar to HyC1 monoclonal antibody, HyC1 scFv could recognize native HEL from carboxymethylated Cys6 and Cys127 HEL (CM 6, 127 -HEL). Comparison of the binding thermodynamics of HyC1 scFv between HEL and CM 6, 127 -HEL showed that the binding enthalpy change was different, while the binding entropy was remained unchanged. The results indicated that the fluctuation of the residual native structure in both HEL and CM 6, 127 -HEL was similar. The NMR experiments for 15 N-labeled HyC1 scFv indicated that the flexibility of HyC1 scFv decreased upon the binding to HEL. Graphical abstract: HyC1 single-chain Fv (scFv) could recognize native HEL from carboxymethylated Cys6 and Cys127 HEL (CM 6, 127 -HEL).